Digestibility and nutritional parameters of corn ethanol coproducts and xylanase for broiler diets - Posadas Mendoza, Lester Josué (2023)
The production of corn ethanol is an activity in constant growth in Brazil and in the world, resulting in many coproducts, such as DDG, DDGS, HP-DDG and HP-DDGS, which can be used in animal feed. Corn ethanol coproducts have a high content of nutrients, such as protein and energy. However, the use of these coproducts in the diet can present nutritional challenges, due to the high fibre content in their composition, which can reduce nutrient digestibility. Thus, the addition of enzymes such as xylanase can be a solution to improve the digestibility of these coproducts and, consequently, the use of nutrients by broilers. The objective was to review the use of corn ethanol coproducts and xylanase in poultry feed, to determine the nutritional value of five diets for broilers from 17 to 25 days containing corn ethanol coproducts from different Brazil´s industries, four corn DDGS and one corn HP-DDG (Exp. I), and to evaluate the effects of the inclusion of xylanase enzyme in diets containing DDGS for broilers from 30 to 36 days on performance, energy values, coefficients of digestibility and gastrointestinal morphometry (Exp. II). In the experiment I, 180 broilers were used, with 17 days of age and an initial average weight of 450.47±17.57 g, distributed in 36 metabolism cages. The experimental design consisted of complete randomized blocks, with six replications per treatment. The treatments consisted of six diets, one reference diet and five test diets containing corn ethanol coproducts, using the total excreta collection method. Differences between the coproducts tested were verified for most of the variables. HP-DDG and DDGS2 showed higher AME and AMEn values (14,129 and 13,929 kJ/kg and 13,431 and 13,276 kJ/kg, respectively) than the other DDGS (P<0,05). For the BWG and FCR there was no difference between the six treatments evaluated (P>0.05). For most of the variables, the HP-DDG showed better nutritional value than the DDGS. Diets containing DDGS4 and HP-DDG showed higher digestible CP values than the DDGS1 and DDGS3 diets (P<0.05). For experiment II, 180 broilers were used, with 30 days of age and an initial average weight of 1228.14±33.49 g distributed in 36 metabolism cages. The experimental design consisted of complete randomized blocks, with six replications per treatment. The treatments consisted of six diets, one reference diet and five diets containing DDGS with the inclusion of xylanase (0, 8,000, 16,000, 24,000 and 32,000 BXU/kg). There was no effect of the addition of xylanase on the AME and GEMC values of the diets containing DDGS or on the AME and AMEn values of the DDGS (P>0.05). However, enzyme inclusion quadratically affected (P<0.05) the ADFDC (45.0256-0.3712x+0.0074x2 ), CPdig (13.5905+0.19462x-0.00519x2 ), EEdig (2.3174+0.10508x-0.00237x2 ) and ADFdig (2.7195- 0.0304x+0.0006212x2 ). NDFdig and ASHdig values increased linearly with enzyme inclusion (P<0.05). For most of the variables, the inclusion of between 18,000 and 22,000 BXU/kg of xylanase showed better results.